NAD METABOLISM IN THE PATHOPHYSIOLOGY AND THERAPY OF PARKINSON’S DISEASE - Illia Koval; Klaudia Romejko; Barbara Kujawa; Jagoda Saniuk; Sandra Sienkiewicz; Justyna Rajczyk; Weronika Kielińska; Joanna Osmólska; Michał Dorota; Kacper Wojtala (International Journal of Innovative Technologies in Social Science, 2025)
This paper explores the rapidly increasing incidence of Parkinson’s disease (PD) and the limitations of current dopamine-based therapies, which only address symptoms rather than underlying causes. This has spurred research into novel treatment approaches rooted in the disease’s pathophysiology. A key pathological hallmark of PD is mitochondrial dysfunction, particularly affecting complex I, a critical component of cellular energy metabolism. This discovery has directed investigations toward individual elements of mitochondrial pathways, including the NAD+/NADH redox balance. Studies indicate reduced NAD+ levels in the brains of individuals with PD, prompting research into the therapeutic effects of NAD+ supplementation. This review summarizes recent scientific findings on how augmenting NAD+ and its derivatives may influence Parkinson’s disease. It discusses the impact of NAD+ precursor supplementation on mitochondrial function and NAD+ levels in neurons carrying the GBA mutation. The paper also covers defects in PINK1 expression, their link to PD development, and the potential role of Nicotinamide (vitamin B3) in this context. Additionally, it assesses the safety of oral NAD+ precursor supplementation and its effects on brain NAD+ levels and metabolism in PD patients. A deeper understanding of PD pathophysiology and continued research into raising NAD+ levels are vital for developing novel therapeutic strategies. Modulating NAD+ holds significant promise as a supportive or disease-modifying therapy for this neurodegenerative condition.